Construction of a Suite of Computable Biological Network Models Focused on Mucociliary Clearance in the Respiratory Tract - Yepiskoposyan, Hasmik; Talikka, Marja; Vavassori, Stefano; Martin, Florian; Sewer, Alain; Gubian, Sylvain; Luettich, Karsta; Peitsch, Manuel Claude; Hoeng, Julia (Frontiers in Genetics, 2019)
Mucociliary clearance (MCC), considered as a collaboration of mucus secreted from goblet cells, the airway surface liquid layer, and the beating of cilia of ciliated cells, is the airways’ defense system against airborne contaminants. Because the process is well described at the molecular level, we gathered the available information into a suite of comprehensive causal biological network models. The suite consists of three independent models that represent 1) cilium assembly, 2) ciliary beating, and 3) goblet cell hyperplasia/metaplasia and that were built in the Biological Expression Language, which is both human-readable and computable. The network analysis of highly connected nodes and pathways demonstrated that the relevant biology was captured in the MCC models. We also show the scoring of transcriptomic data onto these network models and demonstrate that the models capture the perturbation in each dataset accurately. This work is a continuation of our approach to use computational biological network models and mathematical algorithms that allow for the interpretation of high-throughput molecular datasets in the context of known biology. The MCC network model suite can be a valuable tool in personalized medicine to further understand heterogeneity and individual drug responses in complex respiratory diseases.